Three-dimensional Numerical Analysis of a Joint Bonded Reinforced with Silica Nanoparticles (SiO2) (Fracture and Structural Integrity, 2020)
Nanostructured adhesives may be defined as those materials whose elements imbedded in an epoxy matrix have dimensions in the 1 to 100 nm range. One of the most interesting aspects of ceramic nanoparticles is that their mechanical properties depend strongly upon the particle size and shape. Silica nanoparticles (SiO2) have different physical and mechanical properties from bulk ceramics. The aim of the present study is to investigate the effect of the nanoparticles rate on the equivalent stress, peeling stress and shear stress as well as the strains developed in the adhesive joint. Three-dimensional finite element models of adhesive joint were developed to determine the stress intensity as well as strain with different nanoparticles rate in the epoxy resin. Dispersion of nanoparticles with different percent in the epoxy resin allows for reinforcing the adhesive. Polymer embedded silica nanoparticles (SiO2) proved to be highly effective.
Keywords: Epoxy; Finite Element Method; Silica; Silica Nanoparticles SiO2; Stress; Strain